A Strategy to Synthesize Ultrahigh-N-Doped Hierarchical Carbons via Induced beta-Sheet from Silk Fibroin by In Situ Electrogelation/Electropolymerization - Liu, Ta-Chung; Li, Tsung-Yu; Hung, Pei-Sung; Liang, Chun-Wei; Wu, Szu-Chen; Wu, Min-Ci; Wu, Wen-Wei; Wu, Pu-Wei; Chen, San-Yuan (My University, 2020)
Silk fibroin (SF) is recognized for its rich nitrogen content and has been explored for its promising potential in energy storage because of its hexagonal pseudographitic structure from the direct transformation of the unique secondary protein beta-sheet peptides of carbonized SF. In this work, we proposed a novel strategy that combined with in situ electrophoresis and electrogelation of SF as well as the electropolymerization of 3,4-ethylenedioxythiophene (EDOT) for producing high-level nitrogen-doped (N-doped) carbons. A high beta-sheet content of SF can be synthesized in a three-dimensional (3D) inverse opaline skeleton via double-network microstructure (physical beta-sheet cross-linking and chemical PEDOT cross-linking) induced by the hydrophobic EDOTs. This synergistic effect regulating SF distribution and balancing the intra/intermoleeular hydrogen bonding among SF results in boosting beta-sheet contents. Herein, this 3D SF/PEDOT composite inverse opal (SPIO) exhibits a much ultrahigh-coneentrated beta-sheets (46.4%) compared to pure electrogelated SFIO with 16.4% of beta-sheets. After subsequent pyrolysis, a high-level (14.7%) N-doped pseudographitic carbon inverse opal is realized. For evaluation as a pseudocapacitor, this high-level N-doped pseudographitic carbon inverse opal shows a capacitance of 342 F g(-1) at 0.5 A g(-1) and a commendable energy density of 31.7 Wh kg(-1) at an ultrahigh power density of 25009 W kg(-1) (at 50 A g(-1)). After galvanostatic charging/discharging at 15 A g(-1) for 10000 cycles, the sample maintains an impressive capacitance retention of 89.8%.
Keywords: silk fibroin; beta-sheet; electrogelation; electropolymerization; inverse opal; N-doped; supercapacitor